Emerging treatments for progressive myoclonus epilepsies. (2nd April 2020) - Riva, Antonella; Guglielmo, Alberto; Balagura, Ganna; Marchese, Francesca; Amadori, Elisabetta; Iacomino, Michele; Minassian, Berge Arakel; Zara, Federico; Striano, Pasquale
ABSTRACT: Introduction : Progressive myoclonus epilepsies (PMEs) are a group of neurodegenerative diseases, invariably leading to severe disability or fatal outcome in a few years or decades. Nowadays, PMEs treatment remains challenging with a significant burden of disability for patients. Pharmacotherapy is primarily used to treat seizures, which impact patients' quality of life. However, new approaches have emerged in the last few years, which try to curb the neurological deterioration of PMEs through a better knowledge of the pathogenetic process. This is a review on the newest therapeutic options for the treatment of PMEs. Areas covered : Experimental and clinical results on novel therapeutic approaches for the different forms of PME are reviewed and discussed. Special attention is primarily focused on the efficacy and tolerability outcomes, trying to infer the role novel approaches may have in the future. Expert opinion : The large heterogeneity of disease-causing mechanisms prevents researchers from identifying a single approach to treat PMEs. Understanding of pathophysiologic processes is leading the way to targeted therapies, which, through enzyme replacement or underlying gene defect correction have already proved to potentially strike on neurodegeneration.